In-house R&D and External Knowledge Acquisition What Makes Chinese Firms Productive? - Philipp Böing; Elisabeth Müller; Philipp Sandner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper analyses the influence of in-house R&D and external knowledge acquisition on the total factor productivity (TFP) of listed Chinese firms for the time period 2001-2010. We find a quantitatively important positive effect of in-house R&D. The achieved level of technological sophistication of Chinese firms is sufficient to benefit from R&D collaboration with domestic partners. We do not find a significant effect for employing inventors with access to international knowledge or for collaborating with international partners. International knowledge acquisition is only effective if conducted via joint ventures, i.e. if it is supported by a deep organizational relationship.
Keywords: O32; O33; O39; 330